Training on processing household organic waste into eco enzyme at 'Aisyiyah Sidoarjo Orphanage - Syamsudduha Syahrorini; Andriani Eko Prihatiningrum; Akhmad Mulyadi; Ida Agustini Saidi (Community Empowerment, 2022)
The catering operation at the Aisyiyah Sidoarjo Orphanage generates about 5-7 kg of organic waste each day. The orphanage does not currently have a waste segregation site, which means that waste is mixed together and wrapped in plastic, which is obviously bad for the environment. In order to maintain cleanliness and environmental health and to improve the orphanage's economy by using Eco Enzyme fluids, the community service's objective is to give orphanage children early training in the processing of organic waste into Eco Enzyme. The method is through lectures and the practice of making eco enzymes. This program produces Eco Enzyme and its fermentation, which can be used to make liquid plant fertilizer, treat burns and itching, clean bathrooms and floors, and dish soap-and-liquid bath soap blend.